An Exploration of Egyptian Facebook Users' Perceptions and Behavior of COVID-19 Misinformation. Issue 4 (2nd October 2021) - Shehata, Ahmed; Eldakar, Metwaly
ABSTRACT: Social media platforms have become an essential source of information for many users. The purpose of the current study is to explore Egyptian social media users' perceptions and behavior in the context of COVID-19 misinformation. The study was conducted in two stages; the first included identifying and categorizing misinformation shared in the Arabic language on Egyptian social media pages, and the second stage involved distributing a questionnaire to capture the users' perceptions and behavior. The study utilized a mixed-methods approach to achieve the research objectives. In all, 1304 questionnaires were retrieved. The findings of the study showed that there are four main types of misinformation shared on social media. The first type is false claims about the virus or treatment of the virus; the second is false information about the government; the third is false content in general or manipulated content, and the last type is conspiracy theories. The findings also revealed that gender and education affect how people deal with and accept misinformation. Additionally, it was found that the spread of COVID-19 misinformation has caused negative feelings among the participants. The study was conducted on a sample of Egyptian participants and Egyptian social media pages on Facebook, hence, the types of misinformation and the results may differ in other countries, depending on the social media platform and other factors that may play a role in the spread of misinformation.